Medicinal plants in the Southeast Asia for treatment and prevention of oral cancer: a systematic review - Ahmad Rokis, Aina Qistina; Hanafi, Muhammad Faezuddin; Ismail, Che Muhammad Khairul Hisyam; Haris @ Harith, Muhammad Salahuddin; Lestari, Widya; Arief Ichwan, Solachuddin Jauhari; Ismail, Azlini (Asociacion Academica de Ciencias Farmaceuticas de Antofagasta (ASOCIFA), 2025)
Context: Oral cancer is the fourth most common type of cancer among Southeast Asian populations. Despite the existence of numerous anti-cancer drugs, the survival rate of oral cancer patients remains moderate. Furthermore, these drugs often lead to adverse side effects. Southeast Asia has massively underexplored medicinal plants and herbs, and can, therefore, offer a promising avenue for new alternative plant-based drugs against oral cancer. Aims: To review Southeast Asian medicinal plants with in vitro and/or in vivo activities against oral cancer, their bioactive compounds, and their mechanisms of actions using a systematic review approach. Methods: A thorough literature search was conducted in five databases, namely, Google Scholar, PubMed, ScienceDirect, Scopus, and Web of Science, following PRISMA 2020 guidelines and using AXIS quality appraisal tool. Results: From 30 final articles included in this review, 23 plants and 13 bioactive compounds were found to exhibit activities against oral cancer with various anti-cancer mechanisms, most commonly via apoptotic induction. Azadirachta indica with the two bioactive compounds (nimbolide and azadirachtin) showed remarkable in vivo and in vitro anti-cancer properties. Allium sativum (garlic), Zingiber officinale (ginger), and Curcuma longa (turmeric), which are readily available and common in daily cooking, also exhibit anti-cancer activities, which suggest that they can offer good preventive measures against oral cancer. Conclusions: Southeast Asian medicinal plants with remarkable potential, such as A. indica, could be considered for future development of therapeutics for the prevention and treatment of oral cancer.